Exploring Nurses’ Experiences in Providing Health Education to Patients with Chronic Diseases: A Qualitative Study - Muh Rusdi; Adi Hermawan (PT. Nasyah Medika Care, 2025)
Background: Chronic diseases require sustained self-management and long-term treatment adherence. Nurses are strategically positioned to provide health education, yet limited evidence explains how they adapt education to patients’ needs while managing organizational and communication barriers in Indonesian healthcare settings. Research Objective: This study explored nurses’ experiences in providing health education to patients with chronic diseases in Makassar, Indonesia. Methods: A qualitative phenomenological study involved 15 registered nurses selected through purposive sampling. Semi-structured in-depth interviews were conducted until data saturation. Recordings were transcribed verbatim and analyzed using Braun and Clarke’s six-phase thematic analysis, supported by NVivo 14. Trustworthiness was established through member checking, field-note comparison, an audit trail, reflexivity, and detailed contextual descriptions. Results: Four themes emerged: health education as integral nursing care; communication adapted to patient needs and health literacy; patient-related and organizational barriers; and adaptive strategies emphasizing family involvement. Nurses used simple language, repetition, practical examples, demonstrations, teach-back, and motivational communication. Limited time, high workload, low health literacy, communication difficulties, inadequate resources, and limited motivation constrained educational effectiveness. Conclusion: Effective chronic disease education is continuous, individualized, and family-inclusive. Healthcare facilities should provide adequate counseling time, educational resources, and professional development in health literacy, teach-back, therapeutic communication, and motivational techniques to strengthen patient self-management outcomes.